Osteodifferentiated Mesenchymal Stem Cells from Bone Marrow and Adipose Tissue Express HLA-G and Display Immunomodulatory Properties in HLA-Mismatched Settings: Implications in Bone Repair Therapy - Montespan, Florent (Hindawi Publishing Corporation, 2014)
Mesenchymal stem cells (MSCs) are multipotent cells that can be obtained from several sources such as bone marrow and adipose tissue. Depending on the culture conditions, they can differentiate into osteoblasts, chondroblasts, adipocytes, or neurons. In this regard, they constitute promising candidates for cell-based therapy aimed at repairing damaged tissues. In addition, MSCs display immunomodulatory properties through the expression of soluble factors including HLA-G. We here analyse both immunogenicity and immunosuppressive capacity of MSCs derived from bone marrow and adipose tissue before and after osteodifferentiation. Results show that HLA-G expression is maintained after osteodifferentiation and can be boosted in inflammatory conditions mimicked by the addition of IFN-γ and TNF-α. Both MSCs and osteodifferentiated MSCs are hypoimmunogenic and exert immunomodulatory properties in HLA-mismatched settings as they suppress T cell alloproliferation in mixed lymphocyte reactions. Finally, addition of biomaterials that stimulate bone tissue formation did not modify MSC immune properties. As MSCs combine both abilities of osteoregeneration and immunomodulation, they may be considered as allogenic sources for the treatment of bone defects.